Temperature-dependent insertion of prolipoprotein into Escherichia coli membrane vesicles and requirements for ATP, soluble factors, and functional SecY protein for the overall translocation process. - Tian, G (1989)
The requirements for the translocation of prolipoprotein into membrane vesicles were examined in an in vitro system. As measured by the eventual modification and processing of the prolipoprotein to form mature lipoprotein, the overall translocation process was found to require ATP hydrolysis, the presence of some heat-labile soluble cytoplasmic translocation factors, and the function of a cytoplasmic membrane protein, SecY/PrlA. However, the initial step of complete insertion of prolipoprotein into the membrane vesicles occurred without apparent requirements of a nucleotide, cytoplasmic translocation factors, or a functional SecY/PrlA membrane protein. Immunopurified prolipoprotein spontaneously inserted into membrane vesicles at elevated temperatures and required ATP and cytoplasmic translocation factors to form mature lipoprotein. The prolipoprotein inserted most efficiently into liposomes made of negatively charged phospholipids, indicating the importance of phospholipids in protein translocation. These results suggest that ATP hydrolysis and the actions of both cytoplasmic translocation factors and a functional SecY/PrlA membrane protein occur at a step(s) after the insertion of the precursors into membrane vesicles. The initial step of spontaneous insertion of prolipoprotein into membranes is in good agreement with membrane trigger hypothesis proposed by W. Wickner (Annu. Rev. Biochem. 48:23-45, 1979) and the helical hairpin hypothesis proposed by D. M. Engleman and T. A. Steitz (Cell 23:411-422, 1981).